Football athlete talent selection using the analytical hierarchy process - Qotimah, N. K.; Rismayadi, A.; Novian, G. (Journal of Physical Education and Sport, 2024)
The process of talent selection in sports faces unique challenges, complicating the identification of appropriate candidates. These challenges arise from the absence of a thorough and equitable method for evaluating talent, which tends to make the talent selection process subjective and has negative impact on athletes. This study aims to establish priority criteria for selecting junior football athletes using the analytical hierarchy process (AHP). A mixed methods research (MMR) approach, which combines both quantitative and qualitative techniques, was used in this investigation. The study identified three main criteria, further detailed in fourteen sub-criteria, based on discussions with football coaches and administrators. Data analysis was performed using the AHP method. This study showed that physical was a priority, anthropometry was a second priority, and technique was a third priority in the selection process for junior soccer athlete talent. In addition, the results of the study based on sub criteria showed that strength was a priority in physical criteria, height was a priority in anthropometry criteria, and shooting was a priority in technique criteria. So, it can be concluded that the AHP method is the right method to use in determining the priority of junior football athlete talent selection. The AHP method produces 14 sub-criteria which are divided into 3 main criteria, where physical is the number one priority in the junior football athlete talent selection process. This study recommends applying the AHP method in the talent selection process for athletes in other sports to achieve results with a high level of objectivity.